PENGARUH PENGGUNAAN BOOKLET TERINTEGRASI NILAI PREVENTIF MATERI SISTEM EKSKRESI MANUSIA TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI FASE F SMA - Salma, Fitra; Hijrah Selaras, Ganda; Helendra; Olvia Rahmi, Fitri (Universitas Cokroaminoto Palopo, 2024)
Adolescents' knowledge about maintaining a healthy excretory system is still low on average. One way to increase students' knowledge is to implement the use of learning resources that promote and prevent health problems of the excretory system in school learning. This research aims to determine the effect of using an integrated booklet on the preventive value of human excretory system material on student learning outcomes. This type of research is quasi-experimental research with a posttest only control design. The instrument used to measure student learning outcomes is in the form of multiple choice questions. The sample class was selected using a saturated sampling technique. Data analysis using the Man-Whitney test obtained a significance result of (0.000) < α value (0.05), so it can be concluded that the use of an integrated booklet with the preventive value of human excretory system material has a positive effect on student learning outcomes.